TRANSFORMASI KEUANGAN DI DAERAH : ANALISIS EFEKTIVITAS BRILINK DI KECAMATAN GUNUNG KERINCI - Bela Ovelia; Wiyan Mailindra (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
This study aims to evaluate the effectiveness of BRILink in enhancing financial inclusion in Gunung Kerinci District, a region with limited banking and digital infrastructure. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation to understand community experiences and perceptions of BRILink services. The findings indicate that BRILink plays a crucial role in expanding access to financial services, overcoming geographical barriers, and fostering local economic growth. However, key challenges include reliance on unstable internet networks and limited cash availability at agents. Additionally, BRILink contributes to improving financial literacy through direct interactions with agents. The results of this study are expected to provide policy implications for local governments and the Financial Services Authority (OJK) in improving digital infrastructure and strengthening the capacity of BRILink agents as a strategy to expand financial inclusion in rural areas.